2018
DOI: 10.1002/nau.23713
|View full text |Cite
|
Sign up to set email alerts
|

The ability of prior urinary cultures results to predict future culture results in neurogenic bladder patients

Abstract: Previous positive urine cultures can provide valuable information regarding future organism and antibiotic susceptibility in individuals with neurogenic bladder. The practise of reviewing the previous urine culture when selecting empiric therapy is likely an effective practise in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In cases of complicated UTIs, a retrospective cohort found that empiric treatment based on culture results in the last 6 months was an inappropriate choice only 23% of the time and empiric therapy based on no prior culture results was inappropriate in choice 67% of the time, where the odds ratio of accurate treatment was 6.9 (95% CI 2.7 to 17.1) if prior culture data were used and 9.8 (95% CI 2.2 to 43.1) if subsequent culture was the same species [47]. For neurogenic patients in a single-arm retrospective study [52], there was 56% correspondence with the same organism and for antibiotic sensitivity correspondence was 77.3% for ciprofloxacin, 78.5% for nitrofurantoin, and 75% for TMP-SMX. Therefore, we advocate that past cultures, if available between recently and up to 1 year ago, should be used to guide therapy chosen over telemedicine visits regarding UTIs.…”
Section: Predicting Susceptibility By Past Culture Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of complicated UTIs, a retrospective cohort found that empiric treatment based on culture results in the last 6 months was an inappropriate choice only 23% of the time and empiric therapy based on no prior culture results was inappropriate in choice 67% of the time, where the odds ratio of accurate treatment was 6.9 (95% CI 2.7 to 17.1) if prior culture data were used and 9.8 (95% CI 2.2 to 43.1) if subsequent culture was the same species [47]. For neurogenic patients in a single-arm retrospective study [52], there was 56% correspondence with the same organism and for antibiotic sensitivity correspondence was 77.3% for ciprofloxacin, 78.5% for nitrofurantoin, and 75% for TMP-SMX. Therefore, we advocate that past cultures, if available between recently and up to 1 year ago, should be used to guide therapy chosen over telemedicine visits regarding UTIs.…”
Section: Predicting Susceptibility By Past Culture Resultsmentioning
confidence: 99%
“…Twenty-three contributed to the narrative summary and are cited in the paper. These included 2 RCTs [36,37], 13 nonrandomized comparative studies [6,8,[38][39][40][41][42][43][44][45][46][47][48], and 7 single group studies [49][50][51][52][53][54][55], and the remaining articles [5,7,39,41,43,46,50,53, included consensus documents, cost-effectiveness analyses, and narrative reviews. Of note, most of our literature review and review of expert opinion was in line with the International Guidelines from the Infectious Disease Society of America (IDSA) and European Society for Microbiology and Infectious Disease (ESMID) recommendations, including choice of antibiotic for first-line therapy [84].…”
Section: Empiric Treatment Of Utimentioning
confidence: 99%
See 1 more Smart Citation
“…The patientreported outcome of antibiotic treatment should be followed up, but repeated urine cultures are not indicated if symptoms have diminished or ceased. In individual patients with recurring symptoms, the history of previous bacterial cultures, resistance patterns and antibiotic treatments may be informative [29].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-three contributed to the narrative summary and are cited in the paper. These included 2 RCTs [36,37], 13 nonrandomized comparative studies [6,8,[38][39][40][41][42][43][44][45][46][47][48], and 7 single group studies [49][50][51][52][53][54][55], and the remaining articles [5,7,39,41,43,46,50,53, included consensus documents, cost-effectiveness analyses, and narrative reviews.…”
Section: Empiric Treatment Of Utimentioning
confidence: 99%